Research on the promotion effect of nutritional supplements on the physical function of tennis players - Jiao, Chendao (Progress in Nutrition, 2021)
As a nutritional supplement, caffeine exists in many sports drinks. To study the promoting effect of caffeine on the physical function of athletes, 20 tennis players from the P.E. Scientific College of Harbin Normal University were randomly divided into group A, in which tennis players drank caffeinated drinks, and group B, in which tennis players drank decaffeinated beverages. The physical functions of the two groups were compared through grip strength, speed, endurance, and tennis test. According to the research results, there was no significant difference in the grip strength between the two groups, but the speed endurance and muscle endurance of group A were higher than those of group B (P < 0.05). In the tennis test, the average speed and maximum speed of group A were also better than those of group B. The experimental results show that caffeine can promote the speed and endurance of athletes and can improve the physical function of athletes.